Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1521/suli.33.1.52.22784
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Questionnaire on Attitudes Towards Suicide (ATTS) and Its Application in a Swedish Population

Abstract: An instrument measuring attitudes toward suicide was developed through two postal questionnaire surveys, 1986 and 1996, approaching general population samples of 700 and 1,000 persons, respectively, and with response rates of 75% and 64%. A 10-factor model was obtained and comparisons between waves revealed an overall more permissive and pro-preventional attitude in 1996. The results implied complex relationships at the aggregated level between attitudes and suicidal behavior, depending on type of suicidal beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
192
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(214 citation statements)
references
References 21 publications
(21 reference statements)
15
192
1
6
Order By: Relevance
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations